Considered Judgment - Elgin, Catherine Z. (Book collections on Project MUSE., 2001)
Philosophy long sought to set knowledge on a firm foundation, through derivation of indubitable truths by infallible rules. For want of such truths and rules, the enterprise foundered. Nevertheless, foundationalism's heirs continue their forbears' quest, seeking security against epistemic misfortune, while their detractors typically espouse unbridled coherentism or facile relativism. Maintaining that neither stance is tenable, Catherine Elgin devises a via media between the absolute and the arbitrary, reconceiving the nature, goals, and methods of epistemology. In Considered Judgment, she argu.